2015
DOI: 10.1177/1469787415574180
|View full text |Cite
|
Sign up to set email alerts
|

Facebook as a tool for learning purposes: Analysis of the determinants leading to improved students’ learning

Abstract: The study described in this article aims to investigate the use of out-of-class communication between students and instructors using Facebook as a means of interaction for learning. How often/how much students use such an online social network and the clarification as to the reasons for online communication are the two exogenous variables used to measure the perceptions that students have about the impact of online social networking on their learning. How students perceive the quality of the content of student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Both parties do so despite of the possible risks they meet while holding this communication, which mostly includes-as they perceive it-issues of privacy and keeping of personal spaces, concerns regarding information sharing that otherwise may not be visible to the "other side", and the broader matter of boundary blurring (Forkosh-Baruch & Hershkovitz, in press). Of course, OCC may be perceived differently by different students, based on, e.g., its setting, frequency, immediacy, and personal characteristics, like student's or teacher's gender (Alghazo & Nash, 2017;Nkhoma et al, 2015;Rester & Edwards, 2007;Young, Kesley, & Lancaster, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Both parties do so despite of the possible risks they meet while holding this communication, which mostly includes-as they perceive it-issues of privacy and keeping of personal spaces, concerns regarding information sharing that otherwise may not be visible to the "other side", and the broader matter of boundary blurring (Forkosh-Baruch & Hershkovitz, in press). Of course, OCC may be perceived differently by different students, based on, e.g., its setting, frequency, immediacy, and personal characteristics, like student's or teacher's gender (Alghazo & Nash, 2017;Nkhoma et al, 2015;Rester & Edwards, 2007;Young, Kesley, & Lancaster, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Others reported the development of skills related to the democratic participation of everyone in the classroom (Alexander & Sapra, ), the promotion of peer teaching and peer assessment (Ravindran et al, ), or the enhancement of social presence in the classroom community (Gordon, ; Razak & Saeed, ). Several studies emphasized the opportunity to foster independent extracurricular student engagement (Clements, ) or to increase students' motivation and engagement even outside the classroom (Ivala & Gachago, ; Lai et al, ; Nkhoma et al, ).…”
Section: Informal Use Of Facebook In Formal Settings Of Learningmentioning
confidence: 99%
“…Previous research findings about the reasons for the interaction between the teacher and the student on social media suggest that teachers interact with their students on the social media to raise students through out-ofschool time (Akiti, 2012), to teach positive attitudes towards the teacher and the lesson that the student has interacted with (Akkoyunlu, Dağhan and Erdem, 2015;Bridges, 2009), and to make students feel more valuable through likes and comments by teachers on students' posts on social media (Atkins, 2010). In addition to this, it is reported that social media can be used by teachers and students to enhance the relationship between teachers and students (Akiti, 2012;Couillard, 2009;Kamnoetsin, 2014), to get informed about school, class, exams and lessons (Atkins, 2010;Nkhoma et al, 2015), and to increase the academic achievement of students (Helou, Rahim and Oye, 2012). It is seen that the research findings are consistent with the research findings in the literature.…”
Section: Findings Discussion and Resultsmentioning
confidence: 99%